Radiosurgery for Five to Fifteen Brain Metastases: A Single Centre Experience and a Review of the Literature - Rogers, Susanne J.; Lomax, Nicoletta; Alonso, Sara; Lazeroms, Tessa; Riesterer, Oliver (Frontiers in Oncology, 2022)
Purpose Stereotactic radiosurgery (SRS) is mainstream for patients with 1-4 brain metastases (BMs) however the management of patients with ≥5 BMs remains controversial. Our aim was to evaluate the clinical outcomes of patients with ≥5 BMs and to compare with published series as a benchmarking exercise. Methods Patients with ≥5 BMs treated with a single isocentre dynamic conformal arc technique on a radiosurgery linac were identified from the institutional database. Endpoints were local control, distant brain failure, leptomeningeal disease and overall survival. Dosimetric data were extracted from the radiosurgery plans. Series reporting outcomes following SRS for multiple brain metastases were identified by a literature search. Results 36 patients, of whom 35 could be evaluated, received SRS for≥ 5 BMs between February 2017 and October 2021. 25 patients had 5-9 BMs (group 1) and 10 patients had 10-15 BMs (group 2). The mean number of BMs in group 1 was 6.3 (5-9) and 12.3 (10-15) in group 2. The median cumulative irradiated volume was 4.6 cm3 (1.25-11.01) in group 1 and 7.2cm3 (2.6-11.1) in group 2. Median follow-up was 12 months. At last follow-up, local control rates were 100% and 90% as compared with a median of 87% at 1 year in published series. Distant brain failure was 36% and 50% at a median interval of 5.2 months and 7.4 months after SRS in groups 1 and 2 respectively and BM velocity at 1 year was similar in both groups (9.7 and 11). 8/25 patients received further SRS and 7/35 patients received whole brain radiotherapy. Median overall survival was 10 months in group 1 and 15.7 months in group 2, which compares well with the 7.5 months derived from the literature. There was one neurological death in group 2, leptomeningeal disease was rare (2/35) and there were no cases of radionecrosis. Conclusion With careful patient selection, overall survival following SRS for multiple BMs is determined by the course of the extracranial disease. SRS is an efficacious and safe modality that can achieve intracranial disease control and should be offered to patients with ≥5 BMs and good prognostic factors.